Application of synthetic peptides to the diagnosis of neurocysticercosis - Fleury, A.; Beltran, C.; Ferrer, E.; Garate, T.; Harrison, LJS; Parkhouse, RME; Garcia, E.; Fragoso, G.; Costa-Cruz, J.; Biondi, G.; Agapejev, S.; Sciutto, E. (Blackwell Publishing, 2003)
We tested the possible diagnostic utility of five Taenia saginata oncosphere-derived synthetic peptides in T. solium neurocysticercosis (NC). The five peptides correspond to protein sequences with high antigenic indexes that were cloned from a T. saginata oncosphere cDNA library. The test samples consisted of cerebrospinal fluid (CSF) samples randomly collected from patients referred from Mexican and Brazilian neurological institutes. Indirect enzyme-linked immunosorbent assays (ELISA) were carried out with the peptides either unconjugated or coupled to carrier proteins, and were compared with results obtained using T. solium cyst fluid as a positive control. For active inflammatory NC, the higher sensibility (93%) and specificity (85%) was obtained with peptides HP6-2 and Ts45W-1, respectively, coupled to ovalbumin, in both Mexican and Brazilian patients. Examining the results of the individual peptide assays in combination, in some instances, improved the sensitivity to 100%.
Keywords: peptides; Taenia solium; neurocysticercosis; diagnosis